Ammonia and orthophosphate removal of tilapia cultivation wastewater with Vetiveria zizanioides - Hefni Effendi; Widyatmoko; Bagus A. Utomo; Niken T.M. Pratiwi (Journal of King Saud University: Science, 2020)
Vetiver is an environmentally friendly plant since it has non-invasive characteristic, has a high level of heavy metal tolerance, and could reduce N and P content originated from organic water pollutants. Tilapia (Oreochromis niloticus) cultivation wastewater, containing high concentration of N and P, was treated with vetiver (Vetiveria zizanioides) in aquaponics with NFT technique. Treatment consisted of triplicate of P1 (tilapia without vetiver); P2 (tilapia and 400 g of wet vetiver) and P3 (tilapia and 800 g of wet vetiver). Treatment of fish cultivation wastewater with vetiver was capable of lowering concentration of NH3 (65.16%), NO2 (27.51%), NO3 (25.05%) in day 7, and NH4 (30.17%), PO4 (42.75%) in day 14. More vetiver density removed more N and P of tilapia culture wastewater. Keywords: Phytoremediation, Vetiver, Tilapia, Ammonia, Orthophosphate